2020
DOI: 10.3233/jad-190890
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of White Matter Microstructure in Subcortical Vascular Mild Cognitive Impairment with and without Depressive Symptoms

Abstract: Background: Depressive symptoms were thought to increase the risk of vascular dementia. Previous studies reported widespread white matter damages in the subcortical vascular mild cognitive impairment (svMCI), but little is known about the mechanism of depressive symptoms in svMCI. Objective: In the current study, we aim to explore the white matter microstructural alterations in svMCI with depressive symptoms, and their associations with clinical measurements. Methods: Fifty-eight subjects including 18 svMCI wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…While some could not demonstrate a long-term association between WMH progression and depression [ 176 ], large confluent WMHs were associated with a higher incidence of depression in individuals over age 60 years [ 83 ], with persistent depressive symptoms, poorer executive function, and cognitive impairment [ 20 , 177 , 178 ]. WMHs especially within cortico–subcortical neuronal circuits can be interpreted as sequelae of microstructural dysfunctions affecting major brain connections, indicating an association between CVD and depression [ 179 , 180 ], whereas, according to others, structural alterations in the cerebellum may underlie the mechanisms of depressive symptoms in patients with LLD [ 181 ].…”
Section: Structural Brain Lesions In Vadmentioning
confidence: 99%
“…While some could not demonstrate a long-term association between WMH progression and depression [ 176 ], large confluent WMHs were associated with a higher incidence of depression in individuals over age 60 years [ 83 ], with persistent depressive symptoms, poorer executive function, and cognitive impairment [ 20 , 177 , 178 ]. WMHs especially within cortico–subcortical neuronal circuits can be interpreted as sequelae of microstructural dysfunctions affecting major brain connections, indicating an association between CVD and depression [ 179 , 180 ], whereas, according to others, structural alterations in the cerebellum may underlie the mechanisms of depressive symptoms in patients with LLD [ 181 ].…”
Section: Structural Brain Lesions In Vadmentioning
confidence: 99%
“…All svMCI patients were enrolled from a previous randomized control study ( Zheng et al, 2022b ), whereas healthy participants were enrolled from community residents by advertisements. Complete recruitment details were described in our prior work ( Lyu et al, 2019 ; Wang J. et al, 2020 ; Xu J. et al, 2020 ; Xu Z. et al, 2020 ). Briefly, the diagnosis criteria of svMCI were performed according to Petersen’s criteria ( Petersen, 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, another study has identified apoptosis and pyroptosis in the cerebellum in a mouse model of VaD 206 . Imaging studies have suggested that white matter changes in the cerebellum may be linked to executive function and memory performance in patients with subcortical vascular MCI 213 . Furthermore, therapeutic stimulation of the cerebellar fastigial nucleus has shown beneficial effects in VaD treatment 214 .…”
Section: Cerebellum and Other Dementiasmentioning
confidence: 99%
“…206 Imaging studies have suggested that white matter changes in the cerebellum may be linked to executive function and memory performance in patients with subcortical vascular MCI. 213 Furthermore, therapeutic stimulation of the cerebellar fastigial nucleus has shown beneficial effects in VaD treatment. 214 Hence, the cerebellum may play a role in the development of VaD.…”
Section: Cerebellum and Vadmentioning
confidence: 99%